From Digital Philanthropy to Sustainable Empowerment: Dompet Dhuafa Riau’s Mechanisms in Fundraising and Trust Building - Khairuddin, Khairuddin; Pipir Romadi; Muhlasin, Muhlasin; Ryan Pratama (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2024)
Dompet Dhuafa Riau’s transition to digital philanthropic management has significantly increased voluntary donations, addressing the concerns of digital philanthropy scholars about the impact of technology on philanthropic interactions. This research aims to uncover the practical mechanisms employed by Dompet Dhuafa Riau in transforming into a digital media-utilizing philanthropic institution. Using a qualitative method with a phenomenological approach, the study reveals a well-established transition pattern that integrates elements of traditional philanthropy into digital activities. Digital media serves as a tool to facilitate voluntary donations from donors, effectively addressing trust issues commonly associated with transitioning to online platforms by ensuring fund allocation emphasizes sustainability. Service, mentoring, and training mechanisms further enhance Dompet Dhuafa Riau’s credibility as a reliable philanthropic institution, strengthening donor confidence and encouraging continued donations. This shift demonstrates that incorporating media into the management of philanthropic organizations creates a complex relationship between philanthropic institutions and the public, mediated by the unique dynamics of digital platforms.